Author Correction: Umbilical cord extracts improve osteoporotic abnormalities of bone marrow-derived mesenchymal stem cells and promote their therapeutic effects on ovariectomised rats - Akira Saito (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.